The Impact of Enhancing CPO Productivity and Production Capacity in the CPO Downstream Industry on Indonesian Biodiesel Production - Adelina Siregar, Indah; Rifin, Amzul; Novindra, Novindra (Jurnal Penelitian Kelapa Sawit, 2025)
Biodiesel is an alternative fuel produced from palm oil processing. Based on production capacity, biodiesel is the second highest palm oil-derived product after cooking oil, at 11.4 million tons, cooking oil at 15.3 million tons, soap and detergent at 3.6 million tons, basic oleochemicals at 1.7 tons and margarine/shortening at 0.8 million tons (Ditjenbun 2019). With such downstream industry capacity, the domestic palm oil downstream industry is estimated to be able to process around 32 million tons of CPO. The simulation results show that the implementation of the DMO policy through an increase in palm oil demand by the biodiesel industry by 10% has an impact on increasing the domestic real price of palm oil by 0.006%, causing an increase in the domestic demand for Indonesian palm oil by 0.05% with an increase in palm oil demand by the biodiesel industry by 0.007%, palm oil demand by other industries by 0.001%. The increase in the DMO policy also impacts biodiesel production by 0.85% so that Indonesia’s domestic biodiesel supply increases by 16.7%, biodiesel exports increase by 6.88% and there is a decrease in the domestic real price of biodiesel by 2.34%. The impact of increasing biodiesel production capacity is that the demand for biodiesel will increase so that the production of biodiesel raw materials, namely palm oil, will increase. With the increase in palm oil production, it will have an impact on the supply of palm oil and the government will export even higher.